Exploring women’s financial education: A systematic analysis of the literature - Santos, Ticiane Lima dos; Antônio, Roberta Veras; Farias, Andrezza Carolina Brito; Lima, Cássia Regina de; Carvalho, Josué de Lima; Martins, Luciana Dias Barros; Hummel, Sucena Silvia (Seven Editora, 2023)
Financial education plays a key role in empowering women in their personal and professional lives. The general objective of this study is to analyze the impact of financial education actions exercised by women in their personal and business lives, through a systematic review of the literature. The methodology adopted in this study consists of a systematic review of the literature, aiming to analyze the financial education actions carried out by women and their impacts on their personal lives and businesses. The results show that the articles converge in a discussion that demonstrates a trend of less access of women to financial education. The studies presented highlight the existence of a gender disparity in access to financial education and highlight the need for additional actions and research in this area. Overcoming this disparity is critical to strengthening women’s ability to make informed financial decisions and contribute to their economic independence and future well-being. DOI:https://doi.org/10.56238/sevened2023.006-033